2018
DOI: 10.1073/pnas.1807765115
|View full text |Cite
|
Sign up to set email alerts
|

Shift from androgen to estrogen action causes abdominal muscle fibrosis, atrophy, and inguinal hernia in a transgenic male mouse model

Abstract: SignificanceInguinal hernia is one of the most common disorders that affect elderly men. A major pathology underlying inguinal hernia is the fibrosis and other degenerative changes that affect the lower abdominal muscle strength adjacent to the inguinal canal. Here we describe a critical role of estrogen and its nuclear receptor that enhance fibroblast proliferation and muscle atrophy, leading to inguinal hernia. Further research may reveal a potential role of estrogen ablation to prevent muscle fibrosis or he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 87 publications
4
38
0
Order By: Relevance
“…Inguinal hernia is a multifactorial disease caused by endogenous factors including age, gender, anatomic variations, and inheritance as well as exogenous factors such as smoking, comorbidity, and outcomes from surgery [14]. Recently, we found that the conversion of testosterone to estradiol by the aromatase enzyme in lower abdominal muscle tissue in a humanized aromatase transgenic mouse model activates pathways for fibroblast proliferation and fibrosis, leading to intense lower abdominal muscle fibrosis, muscle atrophy, and inguinal hernia; fortunately, an aromatase inhibitor entirely prevents this phenotype [49]. In the present study, we explored the inherited aspects of inguinal hernia formation via data mining of inguinal hernia-causative genes exported from the OMIM database.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Inguinal hernia is a multifactorial disease caused by endogenous factors including age, gender, anatomic variations, and inheritance as well as exogenous factors such as smoking, comorbidity, and outcomes from surgery [14]. Recently, we found that the conversion of testosterone to estradiol by the aromatase enzyme in lower abdominal muscle tissue in a humanized aromatase transgenic mouse model activates pathways for fibroblast proliferation and fibrosis, leading to intense lower abdominal muscle fibrosis, muscle atrophy, and inguinal hernia; fortunately, an aromatase inhibitor entirely prevents this phenotype [49]. In the present study, we explored the inherited aspects of inguinal hernia formation via data mining of inguinal hernia-causative genes exported from the OMIM database.…”
Section: Discussionmentioning
confidence: 98%
“…Inguinal hernia formation is associated with increased lower abdominal muscle tissue fibrosis and muscle atrophy [49]. The exact role of these essential and common downstream proteins and the related signaling pathway in fibroblasts and myocytes of lower abdominal muscle tissue is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1960, Hazary and Gardner reported that male mice given estrogen for prolonged periods developed inguino-scrotal hernias (66). A very recent study by Zhao et al has also revealed that the shift from androgen to estrogen causes inguinal hernia in male mice, and this effect could be entirely prevented by an aromatase inhibitor (67). Tamoxifen is a commonly used selective estrogen receptor modulator that has been used for hormonal treatment of breast cancer for a long time now (68, 69).…”
Section: Discussionmentioning
confidence: 99%
“…Hong Zhao et al found a link between hormones and hernias accidentally while experimenting on a murine model for breast cancer research. 1 They had created humanized transgenic mice by genetically modifying them to carry the human gene for aromatase. Aromatase is a key enzyme for conversion of testosterone into oestrogen.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Hence a corollary which follows this observation is that therapy with aromatase inhibitors could possibly prevent the occurrence of a hernia or prevent recurrence. 1 Body mass index (BMI) has been linked to the aetiology of inguinal hernia. 2,3 However the association at times seems to be confusing.…”
Section: Review Of Literaturementioning
confidence: 99%